Association of systemic immune inflammatory index with all-cause and cause-specific mortality in hypertensive individuals: Results from NHANES - Cao, Yang; Li, Pengxiao; Zhang, Yan; Qiu, Miaohan; Li, Jing; Ma, Sicong; Yan, Yudong; Li, Yi; Han, Yaling (Frontiers in Immunology, 2023)
Background: The relationship between the systemic immune inflammatory index (SII) and the prognosis of hypertensive patients is unclear. This study aims to explore the association of SII with all-cause and cause-specific mortality in patients with hypertension. Methods: This study included 8524 adults with hypertension from the National Health and Nutritional Examination Surveys (NHANES) 2011–2018, and followed for survival through December 31, 2019. Cox proportional hazards models were used to investigate the associations between SII and mortality from all causes, cardiovascular disease (CVD), and cancer. Restricted cubic spline, piecewise linear regression, subgroup and sensitivity analyses were also used. Results: During a median follow-up of 4.58 years, 872 all-cause deaths occurred. After adjusting for covariates, higher SII was significantly associated with an elevated risk of CVD mortality. There was a 102% increased risk of CVD mortality per one-unit increment in natural log-transformed SII (lnSII) (P < 0.001). Consistent results were also observed when SII was examined as categorical variable (quartiles). The associations of SII with all-cause and cancer mortality were detected as U-shaped with threshold values of 5.97 and 6.18 for lnSII respectively. Below thresholds, higher SII was significantly associated with lower all-cause mortality (HR=0.79, 95%CI=0.64-0.97) and cancer mortality (HR=0.73, 95%CI=0.53-1.00). Above thresholds, SII was significantly positive associated with all-cause mortality (HR=1.93, 95%CI=1.55-2.40) and cancer mortality (HR=1.93, 95%CI=1.22-3.05). The results were robust in subgroup and sensitivity analyses. Conclusion: Higher SII (either as a continuous or categorical variable) were significantly associated with a higher risk of CVD mortality. The U-shaped associations were observed between SII and all-cause and cancer mortality.